The treatment of displaced intra-articular distal radius fractures in elderly patients - Bartl, Christoph; Bruckner, Thomas (Deutsches Ärzteblatt, 2014)
Background: From 2000 to 2012, the annual incidence of inpatient treatment for distal radius fracture in Germany rose from 65 to 86 per 100 000 persons. It is unclear whether open reduction and volar angle-stable plate osteosynthesis (ORIF), a currently advocated treatment, yields a better functional outcome or quality of life than closed reposition and casting. - Methods: In the ORCHID multi-center trial, 185 patients aged 65 and older with an AO type C distal radial fracture were randomly assigned to ORIF or closed reposition and casting. Their health-related quality of life and hand/arm function were assessed 3 and 12 months afterward with the Short Form 36 (SF-36) questionnaire and the Disability of the Arm, Shoulder and Hand (DASH) questionnaire. The radiological findings, range of movement of the wrist, and EuroQol-5D (EQ-5D) scores were documented as well. - Results: Among the 149 patients in the intention-to-treat-analysis, there was no significant difference in SF-36 scores between the two treatment groups at one year (mean difference, 3.3 points in favor of ORIF; 95% confidence interval, -0.2 +6.8 points; p = 0.058). The DASH scores showed moderately strong, but clinically unimportant effects in favor of ORIF, and there was no difference in EQ-5D scores. ORIF led to better radiological results and wrist mobility at 3 months, with comparable results at 12 months. 37 of the patients initially allotted to nonsurgical treatment underwent secondary surgery due to significant loss of reduction. - Conclusion: The findings with respect to mobility, functionality, and quality of life at 12 months provide marginal and inconsistent evidence for the superiority of volar angle-stable plate osteosynthesis over closed reduction and casting in the treatment of intra-articular distal radius fractures. Primary nonsurgical management is also effective in suitable patients. ►Cite this as: Bartl C, Stengel D, Bruckner T, Gebhard F and the ORCHID Study Group: The treatment of displaced intra-articular distal radius fractures in elderly patients—a randomized multi-center study (ORCHID) of open reduction and volar locking plate fixation versus closed reduction and cast immobilization. Dtsch Arztebl Int 2014; 111: 779-87. DOI: 10.3238/arztebl.2014.0779
Gesehen am 04.08.2020